Patient perspectives on telemedicine during the COVID-19 pandemic: a mixed-methods community-based study - Marije J. Splinter; M. Kamran Ikram; Charles W. Helsper; Patrick J.E. Bindels; Evelien I.T. de Schepper; Silvan Licher (BMC Health Services Research)
Abstract Background Detailed community-based perspectives on patient experiences with telemedicine are currently lacking, yet essential to assess clinical applicability of telemedicine during and beyond pandemics, alike COVID-19. The aim of this study was to expose patient perspectives on virtual compared to in-person consultations, including determinants of these preferences. Methods We invited 5864 participants of the population-based Rotterdam Study to fill in a validated questionnaire using both close-ended and free-text questions. The questionnaire was sent on 30 July 2020, following a period of lockdowns and closures of non-essential workplaces. It assessed preferences for physician contact, healthcare utilisation, socioeconomic factors, and overall health. Those who experienced at least one virtual consultation (telephone or video call) between March 2020 and the beginning of July 2020 were asked whether those consultations were more, equally or less pleasant than in-person consultations, and to detail their experiences through free-text comments. These narrative data were examined using thematic analysis. Results 4514 participants completed the questionnaire (response rate 77.0%, 58.7% women, mean age 70.8 ± 10.5 years). 1103 participants (24.4%) reported having had experience with virtual consultations. Half of these participants considered virtual consultations less pleasant than in-person consultations (N = 556; 50.4%), while 11.5% found it more pleasant. In total, we coded free-text comments of 752 participants. Prominent themes behind patient preferences for virtual or in-person consultations were lack of nonverbal communication, lack of physical examination, consultation scheduling, personal circumstances, and the presence of somatic and/or language barriers. Conclusions Based on the experiences of a large elderly patient population, we showed that preference for virtual or in-person consultations is dependent on personal and situational variety, and their interplay. Healthcare providers should consider patients’ complex care needs and evaluate the potential added value of nonverbal communication and physical examination before scheduling a virtual consultation.